PEMBELAJARAN IBADAH PRAKTIS BAGI SISWA DI MTS AL-MUKLISIN HUTA III PETANI BARAT - Inggit Prabowo, Muhammad; Saragih, Sokon (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Abstract Practical worship learning is an essential aspect of Islamic religious education aimed at shaping students’ character and enhancing their understanding of the correct and Sharia-compliant ways to perform worship. This study aims to describe the practical worship learning process for students at MTS Al-Muklisin Huta III Petani Barat and to analyze the effectiveness of the methods used in the learning process. The research method employed is qualitative descriptive, with data collected through observation, interviews, and documentation. The results show that practical worship learning at MTS Al-Muklisin has been conducted using a direct and routine practice approach that actively involves students. Demonstration and hands-on practice methods proved effective in improving students’ skills and understanding of practical worship. However, there are some obstacles, such as limited facilities and learning time, which need to be addressed to optimize learning. This study recommends the development of more innovative learning methods and facility support to make practical worship learning more effective and meaningful.